2000
DOI: 10.1180/000985500547250
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and geochemical characteristics of late Cretaceous bentonite deposits of the Kelkit Valley Region, northern Turkey

Abstract: Late Cretaceous bentonitic clays in the Kelkit Valley region of Turkey are composed of an alternation of limestone lenses and silicified tuff nodule-bearing pyroclastic rocks and their alteration products. Quartz, feldspar, biotite, trace amounts of augite together with pumice and volcanic rock fragments comprise the volcanogenic components. Diagenetic minerals are represented by clay, calcite, opal-CT, zeoliteand dolomite. The clay fraction is dominated by smectite and lesser amounts of I-S, illite, chlorite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…According to Borchardt (1977), formation from the group 2:1 type of smectite minerals could be supposed after the addition of little iron. Moreover, Yalcin and Gumuser (2000) reported that clay fraction is dominated by smectite and lesser amounts of I-S, illite, chlorite and kaolinite in Kelkit Valley. Finally, Kılıç (1987) reported the similar consequences in two soil profile that represent reddish chestnut soils in the lower Kelkit Basin (Tokat province).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Borchardt (1977), formation from the group 2:1 type of smectite minerals could be supposed after the addition of little iron. Moreover, Yalcin and Gumuser (2000) reported that clay fraction is dominated by smectite and lesser amounts of I-S, illite, chlorite and kaolinite in Kelkit Valley. Finally, Kılıç (1987) reported the similar consequences in two soil profile that represent reddish chestnut soils in the lower Kelkit Basin (Tokat province).…”
Section: Discussionmentioning
confidence: 98%
“…Thirteen great soil groups recognized in the area can be summarized as brown forest (46.54%), noncalcerous brown forest (14.08%), brown (12.60%), chestnut (6.08%), stony-rocky areas (5.63%), noncalcerous brown (4.56%), high mountain-rangeland (3.51%), alluvial (2.85%), colluvial (2.34%), reddish brown (1.10%), grey brown podsolic (0.63%), hydromorphic (0.06%), and salty-alkaline (0.03) (KHGM 2002). Quartz, feldspar, biotite, trace amounts of augite together with pumice and volcanic rock fragments are the volcanogenic components of the region, while diagenetic minerals are represented by clay, calcite, opal-CT, zeolite and dolomite (Yalcin and Gumuser 2000).…”
Section: Study Areamentioning
confidence: 99%
“…Çerikçioğlu and Yalçın, 1998;Yalçın and Gümüşer, 2000;Bozkaya, 2002, 2003;Yalçın et al, 2005) According to KI and AI (∆°2θ) data; The Kayabaşı formation has low grade diagenesis, the Dedemli formation has high grade formation and the Mahmut Tepesi formation has high grade digenesis and anchizone degree. With increasing degree of diagenesis the smectite component of illites decreases.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…In addition to volcanic glass and/or matrix, typical in volcanogenic rocks, it is considered by many investigators (Yalçın and Gümüşer, 2000;Yalçın and Bozkaya, 2003;Yalçın et al, 2005), who studied in similar environments, that the cations, which occur by the decomposition of K-feldspars with sea water and not used in other phyllosilicate structure, caused the formation illite/muscovites: In all geological times, the chlorites in sedimentary rocks are observed as residual in degradation profiles starting from the regressive metamorphism or diagenesis of the host-rock. However, they were Gat et al, 1996; magmatic water composition from Taylor, 1968). derived either from the alteration zones or completely from the alteration of green schists in which the whole component is chlorite in sedimentary basins.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…In nature, alteration minerals in different rock units of different geological environments, such as marine, lacustrine, fluvial, detrital, etc., develop either by direct precipitation from solution or transformation from other precursor minerals and amorphous materials, or detritally due to diagenesis, weathering, or hydrothermal processes (Velde 1985). Hydrothermal alteration is very common in the Eastern Black Sea Region due to volcanogenic massive sulfide mineralization (Ç agatay 1993;Akçay 2004;Ç elik et al 1999) and in situ alteration of volcanic units in different parts of the region (Yalçın and Gümüşer 2000;Abdioglu and Arslan 2005;Arslan et al 2006). To the best of our knowledge, no detailed mineralogical research concerning the alteration process and distribution of alteration products were previously conducted in the Zonguldak region.…”
Section: Introductionmentioning
confidence: 99%